The emotional consequences of negative personalist framing in the 2023 Spanish general election - Crespo-Martínez, Ismael; Mora-Rodríguez, Alberto; Rojo-Martínez, José Miguel (Frontiers in Political Science, 2025)
IntroductionThe purpose of this research is to analyse the effects of the emotional reactions caused by the negative personalist “repeal Sanchismo” frame on voting for the main party that supported this frame (Partido Popular—PP) and for the party whose leader it was attacking (Partido Socialista Obrero Español—PSOE). In addition, the aim is to determine how these emotional reactions impacted on feelings toward Alberto Núñez Feijóo (PP) and Pedro Sánchez (PSOE).MethodsWe used the dataset of the Third National Survey on Political Polarization in Spain, based on a representative sample of the Spanish population (n = 1,223). Binary logistic regression (BLR) and ordinary least squares (OLS) linear regression techniques were then applied.ResultsFear and anger toward the “repeal Sanchismo” frame increased the likelihood of voting for the PSOE and the sympathy expressed toward Pedro Sánchez. Furthermore, the emotions linked to this frame revealed more behavioral and attitudinal consequences than those connected to the frame proposed by the left (“stop the reactionary wave”), which did not adopt a “negative personalization” focus.DiscussionPersonalization and polarization are two defining features of contemporary electoral campaigns that are also closely linked. The emotional reactions achieved by electoral strategies of negative personalist framing are more polarized and also more influential on voting behavior and political attitudes; however, they can lead to undesired effects of consolidating the adversary, which harm the interests of those that put them into practice.